Wildfowl counts in the British Isles 1954-55 - Atkinson-Willes, G (Wildfowl, 1956)
The Wildfowl Count season of 1954-55 proved to be the most successful so far. A record number of waters were counted regularly, 40 more than in the previous season, and a peak total of almost a quarter of a million wildfowl were observed. This most satisfactory progress is best demonstrated by Table I which shows the number of waters covered regularly each month throughout the season and the number of those for which occasional or sporadic returns have been received. The response to the request for information on wildfowl on minor waters is reflected in the increase in the number of occasional counts. Last season 122 waters were covered for the first time, 53 of them regularly, bringing the total of waters for which information of varying quality is available to about 1225.